Вы находитесь на странице: 1из 85

1- -

I S:1
1? y = F ( x ) y = f ( x ) X,
x X
-: F ( x ) = f ( x )
-: F ( x ) = f ( x )
-: F ( x ) = f ( x )
-: F ( x ) = f ( x )
I S:2
1? f ( x ) = cos 2 x
-: 2 sin 2 x + C
-: 2 sin 2 x + C
1
2

-: sin 2 x + C
-:

1
sin 2 x + C
2

I S:3
1? f ( x ) = sin

x

2

1
x
cos + C
2
2
1
x
-: cos + C
2
2
x
-: 2 cos + C
2
x
-: 2 cos + C
2

-:

I S:4
1? f ( x ) = cos

x

2

1
x
sin + C
2
2
x
- : + 2 sin + C
2
1
x
- : sin + C
2
2
x
- : 2 sin + C
2

-:

I S: 5
1? f ( x ) = xe x
2
- : 2e x + C
2

1
2

- : ex +C
2

- : xe x + C

-:

1 x2
e +C
2

I S:6
1? f ( x ) = e 2 x
1
2

- : e2x + C
- : e2x + C
1 2x
e +C
2
- : 2e 2 x + C

-:

I S:7
1? f ( x ) = sin 2 x
1
cos 2 x +
2
1
- : cos 2 x +
2
- : 2 cos x + C
- : 2 cos 2 x + C

-:

I S:8
x

1? f ( x ) = e 2 +1
x

- : 2e 2 +1 +
x
1 2 +1
-: e
+
2
x

- : e 2 +1 +
x

- : e 2 +1 +
I S:9
1? f ( x)dx = F ( x) +C , f (ax +b) dx =
- : F (x ) + C
- : F (ax + b) + C
1
F ( ax + b) + C
a
- : F ( x ) +C

-:

I S : 10
1? sin xdx =
- : cos x + C
- : cos x + C
- : sin x + C
- : sin x + C
I S : 11
1? a x dx =
- : a x +C

- : a x ln a + C
-:

ax
+C
ln a

-:

ln a
+C
ax

I S : 12
1? a 3 x dx =
- : a3x + C
- : a 3 x ln a + C
-:

a 3x
+C
3 ln a

-:

ln a
+C
ax

I S : 13
1? sin( 4 x + 3) dx =
1
4

- : cos( 4 x + 3) + C
-:

1
cos x + C
4

- : cos( 4 x + 3) + C
-:

1
cos( 4 x + 3) + C
4

I S : 14
1? f ( x ) dx = F ( x ) + C , f (ax )dx =
- : F ( x ) + C
- : aF (ax ) + C
-:

1
F ( ax ) + C
a

- : F ( x ) +C
I S : 15

1? f ( x ) = e
2x

3 3 +1
e
+
2
2x
+1
2
- : e 3 +
3

-:

2x

- : e 3 +1 +
2x
1 3 +1
-: e
+
2
I S : 16
1?

dx
=
a2

2x
+1
3

-:

ln x + x 2 +a 2 +C

x a

- : 2a ln x + a + , a 0
- : ln
-:

x a
+C
x +a

1
ln x + x 2 + a 2 + C
2a

I S : 17
1?

dx
x +a2
2

-:

1
ln x + x 2 + a 2 + C
2a

-:

ln x + x 2 +a 2 +C

x a

- : ln x + a +C
-:

1
x a
ln
+C
2a
x +a

I S : 18
a
1? x dx , a 1,
x a 1
+C
a
x a +1
+C
-:
a +1
xa
+C
-:
a
x a 1
+C
-:
a 1

-:

I S : 19
1?
-:
-:
-:
-:

dx

=
a x2
x
arcsin
+C
a
1
x
arctg + C
a
a
1
x
arcsin
+C
a
a
x
arctg + C
a
2

I S : 20
1?

dx
=
x

- : ln x +C
- : ln x
- : ln x
- : ln x + C

I S : 21
1? cos dx =
- : sin x + C
- : sin x
- : sin x
- : sin x + C
I S : 22
dx
=
1?
cos 2 x
- : ctgx +C
- : tgx +C
- : ctgx
- : tqx
I S : 23
1?
-:
-:
-:
-:

dx

=
a x2
x
arccos + C
a
1
x
arccos
+C
a
a
1
x
arcsin + C
a
a
x
arctg + C
a
2

I S : 24
dx
=
1? 2
a + x2

x
+C
a
1
x
- : arcsin + C
a
a
1
x
- : arctg + C
a
a
x
- : arctg + C
a

- : arcsin

I S : 25
1? F ( x ) - y = f (x ) X ,

- : F ( x) + C , C -
- : F ( x ) + , -
- : F ( x) + f ( x)
- : F ( x ) + f ( x)
I S : 26

1? ( f ( x )dx ) =
- : f ( x)
- : f (x)

- : f ( x) dx
- : F ( x ) +C , F ( x) f ( x ),
-
I S : 27
1? d ( f ( x ) dx ) =
- : f ( x)
- : f ( x) dx
- : f (x)
- : F ( x ) +C , F ( x) f ( x ),

I S : 28
1? dF ( x ) =
- : F ( x) +C , -
- : F ( x) + C , -
- : F (x )
- : F ( x ) dx
I S : 29
1? ( f 1 ( x ) + f 2 ( x)) dx =
- : f1 ( x) + f 2 ( x )
- : f1 ( x) dx + f 2 ( x ) dx

f1 ( x)dx f 2 ( x)) dx
- : f1 ( x ) dx f 2 ( x )dx
-:

I S : 30
1? dx =
- : x +C
-: C
- : x +
- : 2x +
I S : 31
1?

f ( x)dx

f ( x + b) dx

= F ( x ) +C

- : F ( x) + C

1
F ( x + b) + C
b
- : F ( x + b) + C
1
- : F ( x) + C
b

-:

I S : 32
1?
-:

dx
2

x a2

1
ln x + x 2 a 2 + C
2a

-:

ln x +

x 2 a 2 +C

x a
+C
x +a
1
x a
ln
+C
-:
2a
x +a

- : ln

I S : 33
1? C f ( x ) dx =
- : f ( x ) dx
- : + f ( x) dx
- : f ( x ) dx
- : f ( x) dx
I S : 34
2

dx

=
1?
3x 7
- : ln 3 x 7 +C
- : 3 ln 3 x 7 +C
1
ln 3 x 7 + C
7
1
- : ln 3 x 7 + C
3

-:

I S : 35
1? :...
- : udv = uv vdu
- : udv = uv + vdu
- : f (( x )) ( x )dx = f (( x )) d (( x )) = f (u )du
- : f (( x )) ( x) dx = f (( x)) d (( x)) = f (u )du
I S : 36
dx

=
1?
x ln x
- : ln(ln x) + C
- : ln ln x +C
- : ln 2 x + C

- : ln

1
+C
x

I S : 37
1?

dx
=
ln x

- : 2 ln x + C
- : ln(ln x) + C
- : ln x + C
-:

1
+C
ln x

I S : 38

dx

=
1?
cos 2 xtgx
- : ln(ln x) + C
1
+C
-:
cos 3 x
- : ln tgx + C
- : ln tgx +C

I S : 39
xdx
=
1? 2
x +5
-:

1
ln( x 2 + 5) + C
2

- : ln( x 2 + 5) + C
1
x
arctg
5
5
1
x
arctg
+C
-:
5
5

-:

I S : 40
1? :
- : udv = uv vdu

- : udv = uv + vdu
- : f (( x )) ( x ) dx = f (( x )) d (( x )) = f (u ) du
- : f (( x )) ( x) dx = f (( x)) d (( x)) = f (u )du
I S : 41
1? x = a Pn (x ) ,
- : ax
- : x a
- : ( x + a )
- : ( x a )
I S : 42
1? x1 , x2 , ..., xn - Pn (x ) a0 -
x n , :
- : Pn ( x) = ( x x1 )( x x2 ) ... ( x xn )
- : Pn ( x) = ( x + x1 )( x + x2 ) ... ( x + xn )
- : Pn ( x ) = a0 ( x + x1 )( x + x2 ) ... ( x + xn )
- : Pn ( x ) = a0 ( x x1 )( x x2 ) ... ( x xn )
I S : 43
1? : ,

- :
- :
- :
- :

I S : 44
1? ,
- :
- :
- :
- :
I S : 45
1? :
:
- :
- :
- :
- :
I S: 46
1? I :
-:

A
( x a) n

A
x a
A
-: n
x a

-:

-:

A
x a

I S : 47
1? II :
-:

A
( x a) n

A
x a
A
-: n
x a

-:

-:

A
x a

I S : 48
1? III :
Mx + N
( x + px + q ) n
N
-: 2
x + px + q
Mx + N
-: 2
x + px + q
A
-:
( x a) n

-:

I S : 49
1? IV :

M
x + px + q
Mx + N
-: 2
x + px + q
A
-:
( x a) n
Mx + N
-: 2
( x + px + q ) n

-:

I S : 50
dx

=
1?
x +5
- : 5 ln x +5 +C

-:

1
ln x + 5 + C
5

-:

ln x +5 +C

-:

1
+C
( x + 5) 2

I S: 51
dx

cos
-:
-:
-:
-:

ctgx + C
tgx +C

ctgx
sin x

I S : 52
dx

=
1?
(x + 5) 3

-:

5
( x + 5) 4

-:

ln x +5

+C

1
+C
4( x + 5) 4
1
+C
-:
2( x + 5) 2

-:

I S : 53
dx

=
1?
( 2 x + 5) 2
1
+C
2( x + 5)
1
+C
-:
2( x + 5) 2
1
+C
-:
3( x + 5) 3

-:

-:

1
+C
2( x + 5)

I S : 54
(2 x + 5) dx
=
1? 2
x + 5x 9
- : 2 x 2 + 5x 9 + C
- : ln x 2 + 5 x 9 + C
- : ln( x 2 + 5 x 9) + C
- : ln x 2 +5 x 9 +C
I S : 55
(6 x 7) dx
=
1? 2
3x 7 x + 9
- : 2 3x 2 7 x + 9 + C
- : ln 3x 2 7 x + 9 + C
- : ln 3 x 2 7 x +9 +C
- : ln( 3x 2 7 x + 9) + C
I S : 56
1? arcsin xdx
- :
- :
- :
- :
I S : 57
1?

arcsin

xdx

1 x2

- :
- :
- :
- :
I S : 58
1? x 2 arcsin xdx
- :
- :
- :
- :

I S: 59

S: y = f ( x ) [ a, ] [ ,b], a < c < b .


-:

f ( x ) dx = f ( x ) dx + f ( x ) dx

-:

-:
-:

f ( x ) dx = f ( x ) dx f ( x ) dx
f ( x ) dx = f ( x ) dx + f ( x ) dx
c

f ( x ) dx = f ( x ) dx f ( x ) dx

I S: 60

S: y = f ( x ) , [ a, b] .
, ,
b

-:

f ( x ) dx = f ( c ) ( b )
a

-:

f ( x ) dx = f ( b ) ( c a )
a

-:

f ( x ) dx = f ( a ) ( c b)
a

-:

f ( x ) dx = f ( c ) ( a b)
a

I S: 61
b

S: f 1 ( x ) f 2 ( x ) [ a, b] ,
b

f ( x ) dx + f ( x ) dx
1

-:

( f ( x ) + f ( x ) )dx

f ( x ) f ( x ) dx
1

-:

( f ( x ) f ( x ) )dx
1

-:

f ( x ) dx + f ( x ) dx
1

-:

I S: 62
b

S: f ( x ) [ a, b] , k ,
b

-:

k f ( x )dx
a

kf ( x ) dx
a

-:

( k + f ( x ) )dx
a

-:

k f ( x )dx
b

-:

f ( x)
dx
k

I S: 63
1

S:
-: 1,5

( x + 1) dx
0

-: 1
-: 0
-: 0,5
I S: 64

cos xdx

S:
-: 2
-: 0
-: 1
-: -1

I S: 65

S:
-: 0
-: 1
-: -1
-: 2
I S: 66

S:
-: 1
-:
-: 0
-: -
I S: 67

sin xdx
0

sin xdx

S:
-: 1
-: -
-:
-: 0

cos xdx
0

I S: 68
S:

y = f ( x ) [ a,b], F ( x ) f ( x ) .

f ( x ) dx

a
-: F(b) F(a)
-: F(a) F(b)
-: f(b) f(a)
-: f(a) f(b)

I S: 69
2

S:
-: ln 2
-: ln 3
-: ln c
-: ln x

dx

x
1

I S: 70
2

S:
-: ln 2
-: ln 3
-: ln c
-: ln x
I S: 71

dx

x
1

S:
-: 0
-: 2
-: 1
-: 3

f ( x)dx
a

I S: 72
b

S:
-: c(b-a)
-: b-a
-: c(a-b)

cdx
a

-: a-b
I S: 73

tg

S:
tg 4 x
+C
-: 4
-:

xd ( tgx )

tg 4 x
+C
4

4
-: tg x + C
4
-: tg x + C

I S: 74
S:

d 1+ x2
1+ x

-: 2 1 + x + C
2

2
-: 2 1 + x + C
2
-: 2 1 x + C
2
-: 2 1 x + C

I S: 75

( x + 1)
S:

( x + 1)

-:
-:
-:
-:

16

+C

16
(
x + 1)

16

( x 1) 16
16
16

+C

+C

16
(
x 1)

I S : 76

-:

16

+C

15

dx

-:
-:
-:

I S : 77

-: 13
-: 11
-: 1
-: 7
I S : 78

-:
-:
-:
-:

I S : 79
() ...
-:
-:
-:
-:
I S : 80
- ,
N, ...
-:
-: N
-:
-: N

I S : 81

.
-:

-:

-:

-:

I S : 82

-:

-:

-:

-:

I S : 83

:
-:
-:5 ,
-:
-:
I S :84

-: A
-: B
-: D
-: C
I S : 85

-:
-:0 ( )
-:
-: ,
I S : 86

-:

-:
-:
-:
I S : 87
, ...
-:
-:
-:
-:

I S : 88

-:

-:

-:

-:

I S : 89

-:

-:

-:

-:

I S : 90

-:

-:

-:

-:

I S : 91

-: 6
-: -6
-: -3
-: -5

2 3

4

I S : 92

-:

1
2

-: -

1
2

4 2

1

-: 2
-: -2
I S : 93

-: 6
-: 8
-:-3

6

4 3

-:-2
I S : 94

-: -

1
2

4

5 2

2

4 8

-: 8
-: 6
-: 10
I S : 95

-: 2
-: 8
-: 4
-: 10
I S : 96

-: -6

2

3 9

-: -3
-: 10
-: -8
I S : 97

-:
-:
-:
-:

2 3

4

6
10
-6
-8

I S : 98

-:
-:
-:
-:

101
210
111

2
-2
1
-1

I S : 100

211

302
120

-: 0
-: 2

-: -2
-: 3
I S : 101

-:
-:
-:
-:

2 1 0
3 2 1
1 1 2

-15
15
3
-3

I S : 102

213

020
001

-: 2
-: 5
-: 4
-: -4
I S : 103

-: 3
-: 0
-: -2
-: 2

310
001
203

I S : 104

203
0 3 0
001

-: 6
-: 0
-: -6
-: 2
I S : 105

0 2 1

-:
-:
-:
-:

001
203

-15
6
4
2

I S : 106

211
3 2 1
015

-: 2

-: 2

2 1 1
3
51 51
2 1 3 1 3 2
+1 +
15 05 0 1

-:

21 2 1
+5
3 1 3 2

-:

3 1 11 2 1
3 +5
05 15 3 2

I S : 107

012
3 0 1
221

-: 2

-: 2

02 12
3
31 21

30 1 01
+
2 2 30

-:

30 102
+
2 21 3

-: 2

12 02 1
2 +
01 31 0

I S : 108

101
2 1 0
0 2 1

-:

21 10
+
20 2 1

-: 2

1 10

02 2 1

-:

-:

01 10

+2

2 1 2 1

01 12

2 1 20

I S : 109
3

= xdx
-: 0<<2

- : 2 3
- : 0 < < 2,5
- : 1 < < 2,5
I S : 110
3

2
= x dx
2

-: 4 9

-: 0 4
-: 0 3
-: 7 < < 9
I S : 111
y = F ( x ) y = f ( x ) X,
x X
-:
-:
-:
-:

F ( x ) = f ( x )
F ( x ) = f ( x )
F ( x) = f ( x)

F ( x ) = f ( x )

I S : 112
x = a, x = b a < b,
Ox y = f ( x ) .

-: ,
-: ,
-: ,
-: ,
I S : 113
, , .
-: [a, b ]
-: [a, b ]
-: [a, b ]
-: [a, b ]
I S : 114
x = a, x = b a < b,
Ox y = f ( x ) .

-: ,
-: ,
-: ,
-: ,
I S : 115
, , .
-: [a, b ]
-: [a, b ]
-: [a, b ]
-: [a, b ]

I S : 116
b

udv

-:

-:

-:

-:

I S : 117
m- , M- y = f ( x )
[a, b ] ,
b

-:

m( b a ) f ( x ) dx M ( b a )
a

-:

m( a b ) f ( x ) dx M ( b a )
a

-:

m( b a ) f ( x ) dx M ( a b )
a

-:

m( a b ) f ( x ) dx M ( a b )
a

I S : 118
f ( x ) [a, b ] , x =(t )
[, ] ,
( ) = a , ( ) = b ,

f ( x )dx =
a

-:

f ((t ))(t )dt

-:

f ( (t ) ) ( t )dt

-:

f ( ( t ) ) ( t )dt

-:

f ((t ) ) (t )dt

I S: 119
f ( x ) [a, b ] , x =(t )
[, ] , () = a , ( ) = b
b

f ( x )dx =
a

f ( (t ) ) (t )dt


-:
-:
-:
-:

I S : 120
f ( x ) [a, b ] , x =(t )
[, ] , .
b

f ( x )dx = f ((t ))(t )dt


-: ( b ) = , ( a ) =
-: f ( a ) = , f ( ) = b
-: () = a, ( ) = b
-: f () = a, f ( ) = b
I S : 121
f ( x ) [a, b ] . ,
OX (,
y = f ( x ) , x = a x =b,
OX ),
b

-:

2 f ( x )dx
a

-:

f ( x )dx
b

-:

2 f
b

( x )dx

-:

f ( x )dx

I S : 122

cos

xdx =

2
-: 2 sin xdx
0

2
-: 2 cos xdx
0

-:

cos

xdx

xdx

-:

sin
0

I S : 123
x = 0 y =
-:
-:
-:
-:

1
x

I S : 124
x = 0

x + 1 0x
y=
x 1 < 0x

-:
-:
-:
-:

I S : 125
x = 0 y = x 2
-:
-:
-:
-:

I S : 126
x = 0

x 2 x 0
y=
1 x = 0
-:
-:
-:
-:

I S : 127

1

y = 2 x 3

?
-: x = 3
-: x = 2
-: x = 1
-: x = 0
I S : 128

y=

x +7
x 2


-: x = 7
-: x = 2
-: x = 2
-: x = 7
I S : 129

y=

x +1
x 2


-: x = 1
-: x = 1
-: x = 2
-: x = 2
130

y=

x
x +3


-: x = 3

-: x = 0
-: x = 3
-: x = 2
131

4

y = 31+x


-: x = 1
-: x = 3
-: x = 4
-: x = 1
132

cos

xdx

-: 0
-: 1
-: -1
-: 2
133

sin

xdx

-:
-:
-:
-:

0
1
-1
2

I S : 134
f ( x ) [a, b ] , k ,

kf ( x )dx =
a

-:

( k + f ( x ) )dx
a

-: k f ( x )dx
a

-: k f ( x )dx
b

-:

f ( x)
dx
k

135
y = cos x
-: cos xdx
-: cos xdx
-: sin xdx
-: sin xdx
136
y = x 2 [1,4]
-: 4
-: 16
-: 1
-: 8

137
y = x 3 [1,2]
-: 8
-: 2
-: 3
-: 1
138
y = sin 3 x . y
-: 3 sin 2 x
-: 3 sin x cos x
-: cos 3 x
-: 3 sin 2 x cos x
139
y = sin 2 x . y
- : 2 sin x
- : sin 2 x
- : cos 2 x
- : 2 sin 2 x
140
y = x 3 . y

-:
-:
-:
-:

3x 2
6x 2
3x

6x

141
y = sin x . y
-: cos x
-: cos x
-: sin x
-: sin x
142
y = sx . y
-: sin x
-: sin x
-: cos x
-: cos x
143
lim

x 5

2 x 9 +1
=
x 5

-: 0
-:
-: 2
-: 0,2
143
x
5 =
lim
x 0
3x
sin

-:

1
15

-:

1
3

-:

1
5

-: 1
145

lim 1
x
x

-: e 1
-: 1
-: 0
-: e
146
lim
x 1

x 1
=
x x +3
2

-: 1
-: 2
-:
-: 0
147
lim

x 0

x
=
x

-: 1
-: 0
-:
-: 2
148
lim

x 1

2 x +1
=
x 2 1

-: 2
-: 0
-: 3
-:
149

lim (1 cos x ) =
x 0

-: 1
-: 2
-:
-: 0
150

lim

x 0

-:
-:
-:
-:

2 x +1
=
x 1

2
1
-1

151
lim

x 1

-:

1
2

-:

-:

4
3

3 x +1
=
x +2

-: 3
151
lim

x 1

x 1
=
x +2

-: 1
-: 0
-: 2
-:

1
3

153
1

lim 1 +
x
x

2x

-: e
-: 0
-:
-: e 2
154
1

lim 1 +

x
2x

2x

-: 0
-:
-: e 2
-: e
155
lim 2 x =
x

-: 0
-: 1
-: 2
-:
155

lim 2 x =

-:
-: 2
-: 1
-: 0
157

lim 2 x =
x

-: 1
-: 2
-:
-: 0
158
x

2x
lim
=
x 5 x +1

-: 0
-: e
-:
-:

2
5

159
7x

4x +3
lim

x
2x 5

-: 0
-: 1

-: e 7
-:
160
4x + 3
lim

x 2 x 1

2x

-: e 2
-:
-: 2
-: 0
161
x

2x
lim
=
x
5 x +1

-: 0
-:

2
5

-:
-:

I S :162
: , ........ ,
. ?
- :
- :
- :
- :
I S : 163
x, y = f ( x ) ,
...
- :
- :
- :
- :
I S : 164
, y , ...
- :
- :
- :
- :
I S : 165

- :
- :
- :
- :
I S : 166
?
-:
-:
-:
-:

I S : 167

-:
-:

-:

-:
I S : 168

-:
-:
-:

-:

I S : 169

-:
-:
-:
-:

I S : 170

-:
-:
-:
-:

I S : 171

-:
-:
-:

-:

I S : 172

-:

-:

-:

-:

I S :173

-:
-:

-:
-:

I S : 174

-:

-:

-:

-:
I S : 175

-:

-:

-:

-:

I S : 177

-:

-:

-:

-:

I S :178

-:

-:

-:

-:

I S : 179

-:

-:

-:

-:

I S : 180

-:0

-:
-:1
- : 1/4
I S : 181
, ...
- : ""
- :
- : ""
- :
I S : 182

-:
-:

-:
-:

I S : 183

-:
-:
-:
-:

I S : 184

- :
- : 0
- :
- : 0
I S : 185

-:

-:
-:

-:
I S : 186

-:

-:

-:

-:

I S : 187

-:

-:
-:

-:

I S : 188
...
- :
- :
- :
- :
I S : 189

- :
- :
- :
- :
I S : 190

- : " 0 " ()
- : " 1 " ()
- :
- : " "
I S : 191
.
, = ?
- : 3,142
- : 2,54
- : 3,62
- : 2,718
I S : 192

- :
- : " 0 " ()
- : " 1 " ()

- : " "
I S : 193

- : " 0 " ()
- : " e " ( )
- :
- : " 1 " ()
I S : 194

- : " 0 " ()
- : " 1 " ()
- : " e " ( )
- :
I S : 195
:
-:

-:

-:

-:

I S : 196

- : " 0 " ()
- : " 1 " ()
- : " e " ( )
- :
I S : 197

-:

-:

-:

-:

I S : 198

-:

-:

-:

-:

I S : 199

-:

-:

-:

-:

I S : 200

-:

-:

-:
-:

I S : 201

- : 2
- : (-1)
- :
- : (-1)
I S : 202

-:

-:

-:

-:

I S : 203

-:

-:

-:

-:

I S : 204

-:
-:

-:
-:

I S : 205

-:

-:

-:

-:

I S : 206

- :
- :
-:1
- :
I S : 207

-:
-:
-:
-:

I S : 208

-:
-:0
- : -1
- : -1
I S : 209

-:

-:

-:

-:

I S : 210
" "?
- :
- :
- :
- :
I S : 211
?
- :
- :
- :
- :
I S : 212

-:
-:
-:
-:

I S : 213

-:
-:

-:
-:

I S : 214

-:

-:

-:

-:

I S : 215

-:

-:

-:

-:

I S : 216

-:

-:
-:

-:

I S : 217

-:
-:
-:

-:

I S : 218

- :
- :
- :
- :
I S : 219

-:

-:

-:

-:

I S : 220

-:

-:

-:
-:
I S : 221
, ...
- :
- :
- :
- :
I S : 222

-:
-:
- : , ,
- :
I S : 223

-:I
- : II
- : III
- : IV
I S : 224

-:I
- : III
- : IV
- : II
I S : 225

-:I
- : II
- : III
- : IV
I S : 226

-:
-:
-:
-:

I S :227

?1 C ( 0,1) 2
-: x 2 + ( y 1) 2 = 4
-: ( x 1) 2 + y 2 = 4
-: ( x 1) 2 + ( y 1) 2 = 4
-: x 2 + ( y 1) 2 = 2
I S :228
? 1 x = a ( a 0 )
-: ,
-: ,
-: ,
-: ,
I S :229
? 1 x = 0
-: ,
-: ,
-: ,
-: ,
I S :230
? 1 y = 0
-: ,
-: ,
-: ,
-: ,
I S :231
? 1 y = b( b 0)
-: ,
-: ,
-: ,
-: ,
I S :232
? 1 , M ( x 0, y 0 ) K

-: y y 0 = K ( x x 0 )
-:

x x1
y y1
=
x 2 x1
y 2 y1

-: Ax + By + x0 = 0
-: Ax 0 + By 0 + K = 0

I S :233
? 1 , M 1 ( x1, y1 ) ( x 2 y 2 )

-:

x x1
y y1
=
x 2 x1
y 2 y1

x 2 x1
y y1
=
x x1
y 2 y1
x 2 + x1
y + y1
=
-:
x + x1
y 2 + y1
x + x1
y + y1
=
-:
x 2 + x1 y 2 + y1

-:

I S :234
? 1 y = 2 x
-: A(1,2 )
-: A( 2,1)
-: A( 3,1)
-: A(3,6 )
I S : 235

- : II
- : III
- : IV
-:I
I S : 236

-:I
- : III
- : II
- : IV
I S : 237

-:
-:
-:
-:

I S : 238

-:
-:

-:
-:

I S : 239

-:b>1
-:b>0
-:b=1
- : b = -1
I S : 240

-:

-:

-:

-:

I S : 241

-:

-:

-:

-:

I S : 242

-:

-:

-:

-:

I S : 243

-:
-:
-:
-:
I S : 244
...
- :
- :
- :
- :

I S : 245
...
- : ,
- :
- : ,
- :
I S : 246

-:
-:
-:

-:

I S : 247

-:
-:
-:
-:

I S : 248

-:
-:
-:

-:

I S : 249

-:

-:
- :
-:

I S : 250
n- ...
-:
-:
-:
-:
I S : 251

-:
-:
-:
-:

I S : 252

-:
-:
-:
-:
I S : 253
n- , ...
- :
- :
- :
- :
I S : 254

- : (8, 1, 3)
- : (2, 4, 3)
- : (8, 4, 12)
- : (2, 1, 12)
I S : 255

- :
- :
- :
- :
I S : 256

- : n
- : n
- : ,
- :
I S : 257
...

-:

-:
-:

-:

I S : 258
...
-:
-:
-:
-:

I S : 259
? 1
y = k1 x + b1 y = k 2 x + b2
-: k1 = k 2
-: k1 = k 2
-: k1 =

1
k2

-: k1 =

1
k2

I S : 260
? 1
y = k1 x + b1 y = k 2 x + b2
-: k1 = k 2

-: k1 = k 2
-: k1 =

1
k2

-: k1 =

1
k2

I S : 261
? 1
-: y = 3 x + 5, y = 3x 4
-: y =

1
x +1, y = 2 x + 7
2

-: y = 3 x + 5, y = 3 x 4
-: y =

1
x +1, y = 2 x + 7
2

I S : 262
? 1
-: y = 3 x + 5, y = 3x 4
-: y =

1
x +1, y = 2 x + 7
2

-: y = 3 x + 5, y = 3 x 4
-: y =

1
x +1, y = 2 x + 7
2

I S : 263
? 1 M ( x 0, y 0 ) Ax + By + C = 0,
-:

-:

d = Ax 0 + By 0 + C

-: d =

Ax + By +C
A2 + B 2

-:
I S : 264
? 1 M ( 0,4) y = 2
-: 2
-: 1
-: 5
-: 4
I S : 265
? 1 A( 3,0 ) B ( 4,0 )
-: 7
-: 3
-: 4
-: 1
I S : 266

? 1 M 1 ( x1 , y1 , z1 ) M 2 ( x 2 , y 2 , z 2 )
-:
-:
-:

-:
I: 267
S:

-: (u +) =u +

-: (u ) = u

u u
u
=
2
-:

c
c
= 2

-:

I S : 268
f ( x ) X ,, f ( x) = const X .

-:
-:
-:
-:

f (x ) X
f (x) X
f (x ) X
f (x) X

I S : 269
, f ( x ) x 0
,..., f ( x0 ) = 0 .

-:
-:
-:
-:
I: 270
S:

-: ( u +) = u +

-: ( u ) = u + u


u u
u
=
2
-:

c
c
= 2

-:

I: 271
S:

-: ( u +) = u

-: ( u ) = u + u

u u
u
=
2
-:

c
c
= 2

-:
I: 272
S:

-: ( u +) = u +

-: ( u ) = u + u

u + u
u
=
2
-:

c
c
= 2

-:
I S: 273
1? I :
-:

A
( x a) n

A
x 2
A
-: n
x a

-:

-:

A
x a

I S : 274
1? II :
-:

A
( x a) n

A
x a
A
-: n
x an

-:

-:

A
x a

I S : 275
1? III :
Mx + N
( x + px + q ) n
N +M
-: 2
x + px + q
Mx + N
-: 2
x + px + q
A
-:
( x a) n

-:

I S : 276
1? IV :
M
x + px + q
Mx + N
-: 2
x + px + q
A +
-:
( x a) n
Mx + N
-: 2
( x + px + q ) n

-:

I S : 277
" "?
- : 1-
- :
- :
- :
I S : 278
?
- :
- :
- :
- :
I S :278
x 0 f ( x )
,
-: x 0 - f ( x )
-: x 0 - f ( x )
-: x 0 - f ( x )
-: x 0 -

I S :279
x 0 f ( x )
,
-: x 0 - f ( x )
f ( x)
-: x 0 -
-: x 0 - f ( x )
-: x 0 -
I S :280

X ,
-:
-:
-:
-:
I S :281

,
-:
-:
-:
-:
I S :282
f (x ) x 0
, .. f ( x 0 ) = 0

-:
-:
-:
-:
I S :283
f (x)
x 0 , x 0 .

-:
-:
-:
-:
I S :284
f ( x )

Lim
x

f ( x)
( f ( x) kx ) = b
= k 0 Lim
x
x

-: y = kx + b f ( x )
-: y=b f ( x )
-: x=b f ( x )
-: x=ky-b f ( x )
I S : 285
,
-:
-:
-:
-:
I S : 286

-:
-:
-:
-:
I S : 287

-:
-:
-:
-:
I S : 288
, { a n } +, ,
A > 0, N, n > N

-: a n < A
-: a n < A
-: a n > A
-: a n > A
I S : 289
, { a n } , ,
A > 0, N , n > N
:
-: a n < A
-: a n < A
I S : 290

f ( x ) x 0
-:
-:
-:
-:
-: a n > A
I S : 291
y = 2 x 2 3 x0 = 5
-: 23
-: 17
-: 20
-: 15
I S : 292

-:

y=

x 3 x

x 0 = 4

1
4

-: 2,75
-:

1
4

-: 2,75
I S : 293
y = e x x0 = 0
-: 1
-: e
-: 0
-: 1
I S : 294
y = x x0 = 9
-:

1
6

-: 3
-: -3
-:

1
6

I S : 295
y = cos x x 0 = 0
-: 0
-: 1
-: -1
-:

1
2

I S : 296

y = sin x x0 =
1
3

-:

2
2

-:
-:

2
2

-:

-: 1

I S : 297
Lim
x 0
-:
-:
-:
-:

tg 2 x

sin 5 x

2,5

5
0,4
0,8

I S : 298
Lim
x

-:

x 2 + 2x 3

3x 2 x 3 + 1

1
3

-: 0
-:

-:

1
3

I S : 299
Lim
x 2

-:

13
16

-:

1
2

x 2 + 2x + 5

2 x 2 x + 10

-: 0
-:

I S : 300
Lim
x 0

-:

2
3

-:

2
5

-:

1
7

-:

2
7

2 x 2 3x + 1

3x 2 + 5 x + 7

I S : 301
Lim
x

-: 0
-:

-:

2
3

-:

3
2

2 x 2 3x + 5

3x 2 + x 7

I S : 302
Lim
x 0
-: 6
-: 1
-: 0
-:

2
3

2tg 3 x

3tg 2 x